2017
DOI: 10.1371/journal.pone.0177556
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effectiveness of a small quantity lipid-based nutrient supplement on reducing anaemia and stunting in refugee populations in the Horn of Africa: Secondary data analysis

Abstract: Stunting and micronutrient malnutrition are persistent public health problems in refugee populations. UNHCR and its partner organisations implement blanket supplementary feeding programmes using a range of special nutritional products as one approach to address these issues. The evidence base for the efficacy and effectiveness of a small quantity lipid-based nutrient supplement, Nutributter®, in reducing stunting and anaemia is limited. Secondary data analysis was used to assess the effectiveness of Nutributte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Of the 58 studies included in the systematic review, according to the Development Human Index, 24 (41.4%) were conducted in regions with very high development human index (Bahrain, Emirates, Kuwait, Oman, Qatar, Saudi Arabia) or high development human index (Egypt, Iran, Jordan, Lebanon, Libya, Tunisia, Algeria) [ 13 , 21 , 23 , 25 , 28 , 32 , 33 , 35 , 36 , 44 , 46 - 49 , 53 , 55 , 59 , 60 , 62 , 64 , 65 , 68 ], 21 (36.2%) were conducted in regions with a medium development human index (Iraq, Morocco, Pakistan, Palestine) [ 14 , 17 - 20 , 26 , 29 , 31 , 34 , 37 , 38 , 42 , 43 , 51 , 52 , 54 , 56 , 58 , 63 , 67 , 70 ], and 13 (22.4%) were conducted in regions with a low development human index (Afghanistan, Djibouti, Sudan, Syria, Yemen, Somalia) [ 15 , 16 , 22 , 27 , 30 , 39 - 41 , 45 , 50 , 57 , 61 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 58 studies included in the systematic review, according to the Development Human Index, 24 (41.4%) were conducted in regions with very high development human index (Bahrain, Emirates, Kuwait, Oman, Qatar, Saudi Arabia) or high development human index (Egypt, Iran, Jordan, Lebanon, Libya, Tunisia, Algeria) [ 13 , 21 , 23 , 25 , 28 , 32 , 33 , 35 , 36 , 44 , 46 - 49 , 53 , 55 , 59 , 60 , 62 , 64 , 65 , 68 ], 21 (36.2%) were conducted in regions with a medium development human index (Iraq, Morocco, Pakistan, Palestine) [ 14 , 17 - 20 , 26 , 29 , 31 , 34 , 37 , 38 , 42 , 43 , 51 , 52 , 54 , 56 , 58 , 63 , 67 , 70 ], and 13 (22.4%) were conducted in regions with a low development human index (Afghanistan, Djibouti, Sudan, Syria, Yemen, Somalia) [ 15 , 16 , 22 , 27 , 30 , 39 - 41 , 45 , 50 , 57 , 61 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 58 observational studies included in the systematic review, eight (13.8%) were conducted in countries involved in a civil war [ 15 , 29 , 30 , 39 , 40 , 45 , 50 , 61 ], 42 (72.4%) were reported from both urban and rural areas, 8 (13.8%) were conducted in urban areas only [ 14 , 24 , 26 , 35 , 36 , 53 , 62 , 67 ], and 8 (13.8%) in rural areas only [ 18 , 32 , 37 , 39 , 42 , 43 , 66 , 70 ]. Also, 7 (12.1%) studies involved refugees [ 15 , 16 , 20 , 22 , 27 , 34 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Being anemic in young age, whether it is from iron deficiency, or parasitic infections, can have negative health consequences in both the short and long runs [118][119][120]. In another cross-sectional study in children residing in Kakuma refugee settlement in northern Kenya, the overall prevalence of anemia ranged between 44 and 77.1% [122]. On the other hand, Gemede et al [34] revealed that there are some accessions with high Fe contents among locally cultivated varieties in western Ethiopia.…”
Section: Contribution To Mineral Dietary Allowancementioning
confidence: 99%
“…In A18 the effectiveness of introducing a small lipid-based supplement to reduce anemia in refugee children from 0 to 59 months of age, not altering the state of dwarfism or acute malnutrition of this population, living in camps in the Horn of Africa. Noting that despite the efforts with fortification and supplementation programs, in addition to food basket donations, to alleviate food and nutritional deficits in refugee camps, malnutrition and macro and micronutrient deficiencies are still perennial 29 .…”
Section: Emerging Diseasesmentioning
confidence: 99%